Peramalan Jumlah Produksi Buah Nanas di Provinsi Riau Menggunakan Metode Single Exponential Smoothing - Sarah Dwi Az-Zahra; Depriwana Rahmi (JMT (Jurnal Matematika dan Terapan), 2024)
Forecasting is an attempt to project future events using relevant information from the past. Using such data, forecasting serves as an effective means of planning activities and reducing the likelihood of errors in predicting the course of future events. One method of prediction is the Single Exponential Smoothing method. The research is aimed at predicting the amount of pineapple production in Riau Province by 2023. The study utilizes information on the number of pines production in the Riau province as many as 10 datasets covering the period from 2013 to 2022. This data is obtained from the official website of BPS Province Riau. In this study, the researchers used quantitative methods. Based on a solver analysis in Ms.Excel, the results showed that the forecast accuracy rate reached 71.64% with the smallest error presentation of about 28.36% which categorized these forecasts quite well. Using this method, the forecast quantity of pineapple production in Riau Province for 2023 is 262,637 tons.